PERANCANGAN KINERJA SISTEM INFORMASI DENGAN METODE BALANCED SCORECARD DAN ANALYTICAL HIERARCHY PROCESS - Retnawati, Lestari (Jurnal IPTEK, 2017)
XYZ University as one of private universities in Surabaya which is quite in demand, has the support of Information Systems and Information Technology in carrying out its academic operational activities. But the existence of the information system has not been fully integrated with the related work units, and there are some information systems that are not used as the information system should be within the Technical Implementation Unit of the Information and Communication Technology (UPT TIK). UPT TIK itself is still less than the maximum in carrying out its duties as a unit that takes care of various things related to academic operational activities. As well as the institution itself does not have a strategic planning of information systems and technology coherent between the vision and mission with operational programs. By looking at the above problems, the constraints of information system performance at XYZ University lies in the system and employees and the inability of the institution to formulate and describe comprehensive strategic planning and strategic planning formulation model. Therefore, the authors conduct research with the title â€œPerformance Design of Information System Using Balanced Scorecard (BSC) and Analytical Hierarchy Process (AHP)â€. Balanced Scorecard is a measure and a management system that views the performance of a business unit from four perspectives: financial perspective, customer perspective, internal business process perspective, and learning and growth perspective. Weighted results for each perspective are: customer perspective (42.8%), internal business process perspective (35.0%), growth and learning perspective (14.4%), and financial perspective (7.8%). Based on the weighting, performance evaluation is done by comparing the performance measurement result against the performance target. Performance evaluation is done by using Traffic Light System.